DANCE MOVEMENT THERAPY (DMT) AS AN EFFORTS TO INCREASE LEARNING CONCENTRATION ON ELEMENTARY SCHOOL STUDENTS - Rahmawati Rahmawati; Bangun Yoga Wibowo; Raudah Zaimah Dalimunthe (JPSD (Jurnal Pendidikan Sekolah Dasar), 2019)
Abstract. The purpose of this study is to obtain information on the benefits of Dance Movement Therapy (DMT) to increased the learning concentration of students at MIN 1 elementary school in Mersi Village, East Purwokerto. This research used a direct survey qualitative method and literature study. Based on the results research, it shows that administration of DMT to elementary students helped in: (1) increased integration of cognition, affection, and physical experience; (2) expressions of competence; (3) increase self-awareness; (4) as a form of coping in an effort to overcome the problem of pressure/stress, mood, emotion; (5) helping to improve self-efficacy (6) DMT is a form of social support. When cognitive integration, affection, self-awareness and happy conditions are achieved, students can improve their concentration in the learning process. The results can be used as a strong basis for the importance of providing DMT therapy in schools of students to assist in the process of improving the results of the learning process. Keywords: dance movement therapy (DMT)